Fully automated immunoassay for quantitative determination of FXIII - Kappel, A.; Stephan, S.; Duwe, C.; Pechmann, L.; Althaus, H.; Ehm, M.; Fischer, B.; Hahn, M.; Schwarz, H.; Vitzthum, F. (Hämostaseologie, 2011)
Coagulation factor XIII (FXIII) is essential for clot stabilization. Deficiency of FXIII is associated with a risk of bleeding and impaired wound healing. Substitution therapy with FXIII remedies for patients with low plasma levels of FXIII requires diagnostic quantification of the factor before and during therapy. Here, we describe a prototype of a preliminary research immunoassay for quantification of FXIII antigen on automated coagulation instruments. The prototype assay is based on a monoclonal antibody (mAb) directed against FXIII A chain, whereas the mAbs are coupled to latex particles. FXIII in a plasma specimen causes agglutination of the latex particles, which can be quantified turbidimetrically. Performance data of the assay prototype processed on BCS® XP and Sysmex® CA-1500 instruments demonstrate a good correlation to the Berichrom® factor XIII activity assay1 from Siemens Healthcare Diagnostics (r = 0.94). Results: Comparability of instruments was excellent (r = 0.98). Coefficients of variation of total imprecision measurements ranged from 2.2 to 3.4%. Linearity was excellent over the range tested (12–121% FXIII). Analytical sensitivity was 0.51% FXIII on BCS XP and 0.44% FXIII on Sysmex CA-1500, respectively. No interference (> 10% bias) was observed with haemoglobin (up to 400 mg/dl), cholesterol (up to 300 mg/dl), bilirubin (up to 60 mg/dl) or triglycerides (up to 3000 mg/dl). Conclusion: The preliminary research assay prototype has the potential for excellent analytical sensitivity, precision, and dynamic range suitable to measure reliably FXIII antigen levels in human plasma.
Keywords: Bleeding; coagulation; factor XIII; factor XIII deficiency; immunoassay